The first mention of the laity in the letter of Clement to the Corinthians - Ivan Muzychka (Українське Pелігієзнавство, 2013)
Leg of St. Paul stepped on the European continent somewhere around the 50th in the time of his second trip from Asia Minor from the glorious Troy to today's Macedonia. Among the Europeans Pavlov's sermon has found a good ground: he founded several communities, traveling, in particular, in Philippi and in Thessalonica. But the apostle also faced a strong opposition, in particular from their Jewish brothers, who sometimes even driven him by force. From the town of Vera Paul, it was necessary to protect the city of Athens, the capital of great glory, science, philosophy, literature, art, architecture, culture. Here, the scientists wanted to listen to Pavlov "a new science" (Acts 17:19). The Pavlov's word on the Aeropagus ended in great failure and highs. Paul left Aithenes cursed, not returning more there, from neglect to "insidious philosophy" as "an empty deception" (Colossians 2: 6).